Role of RhoGDIα on migration and invasion of estrogen receptor positive MCF7 and estrogen receptor negative MDA-MB-231 breast cancer cells - Hooshmand, Somayeh (2014)
Breast cancer arises from changes in gene and protein expression of a normal cell. These changes have been correlated with a number of cellular processes, including growth control, apoptosis, tumorigenesis and metastasis. Rho GDP dissociation inhibitor (RhoGDI) family of proteins can inhibit cell motility, invasion, and metastasis in cancer cells by inactivating the RhoGTPases. Rho GDP dissociation inhibitor α (RhoGDIα) in particular, a member of RhoGDI family, has been consistently shown to interact with the estrogen receptor (ER) resulting in a change to its transcriptional activity which is inversely correlated with cell motility and invasion in breast cancer. The consequence of RhoGDIα activity on migration and invasion of estrogen receptor positive (ER+) and negative (ER-) breast cancer cells is not clear. The main objective of this study was to investigate the consequence of RhoGDIα activity on migration and invasion of ER+ and ER- breast cancers cells. The first specific objective is to observe the likely possible opposing effect of RhoGDIα on migration and invasion of ER+ (MCF7) and ER- (MDA-MB-231) breast cancer cells with or without 17β-estradiol (E2), since the interaction of E2 with ER has been shown to induce cell proliferation. These cells were treated with E2 to assess whether exposure of these cells to E2 affected the level of RhoGDIα. The RhoGDIα was silenced by short interfering RNA (siRNA) and overexpressed using GFP-tagged ORF clone of RhoGDIα and cell transfection was performed with Lipofectamine. More than 90% RhoGDIα gene silencing in these cells was confirmed both at mRNA and protein levels by qRT-PCR and Western blot. Successful RhoGDIα overexpression was also confirmed by flow cytometry and Western blot in both cell lines. There was no significant difference in the RhoGDIα mRNA expression with or without E2 in these cell lines. However, using migration and transwell invasion assays, it was found that silencing of RhoGDIα in MCF7 and MDA-MB-231 cells significantly increased migration and invasion of these cells. Overexpression of RhoGDIα in MCF7 cells suppressed their migration and invasion, but this was not significant on MDA-MB-231 cells. These results indicate that the silencing of RhoGDIα similarly affects in vitro migration and invasion of ER+ MCF7 ii and ER- MDA-MB-231 cells. However, in vitro migration and invasion assays are differently affected by the overexpression of RhoGDIα in these two cell lines and this may be due to the differences in ER expression, primary invasive ability and/or other molecules between these two cell line models, which warrant further investigation. In the second specific objective comparative proteome analysis of the RhoGDIα function in MCF7 and MDA-MB-231 breast cancer cells was performed in order to identify the protein expression changes potentially involved in invasion and migration. These cells were subjected to two-dimensional electrophoresis after RhoGDIα silencing and overexpression and spots of interest identified by matrix-assisted laser desorption/ionization time of- flight/time-of-flight mass spectrometry. The results showed a total of 35 proteins that were either up- or down-regulated in these cells. Here, 9 and 15 differentially expressed proteins were identified in silencing of RhoGDIα MCF7 and the MDA-MB-231 cells, respectively. In addition, 10 proteins were differentially expressed in the overexpression of RhoGDIα in MCF7, while only one protein was identified in the overexpression of RhoGDIα MDA-MB-231. A large proportion of the identified proteins in this study have been previously indicated in tumorigenesis and invasiveness of breast cancer cells such as Profilin1, Apolipoprotein E, Catechol-O-methyl transferase, Smac/DIABLO, programmed cell death 6, ATP synthases α-subunit, NADH dehydrogenase (ubiquinone) Fe-S protein, peroxiredoxin 2, EF-Tu, Eukaryotic translation initiation factor 4E, Rho GDP-dissociation inhibitor 2, Calpain small subunit 1, RNA-binding protein 8a, protein L-isoaspartyl Omethyltransferase, Growth factor receptor-bound protein 2 and Peroxiredoxin III. However, not much is known on the function of adenine phosphoribosyl transferase, dCTP pyrophosphatase 1, fumaryl acetoacetate hydrolase domain-containing protein 1, Proteasome subunit beta type-4, GTP-binding protein SAR1a, Protein Hikeshi, Integrin alpha-M, GrpE protein homolog 1 mitochondrial in breast cancer. Hence, these proteins may serve as useful candidate biomarkers for tumorigenesis and invasiveness of breast cancer cells. Future studies are needed to determine the mechanisms by which these proteins regulate cell migration to explain the observed differences of the invasion and migration of MCF7 and MDA-MB-231 cells in response to RhoGDIα overexpression. The combination of RhoGDIα with these or other biomarkers might be a more promising approach in inhibition of cancer migration.